2013
DOI: 10.1523/jneurosci.0288-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Restoration of Spines and their Synapses in L-DOPA-Induced Dyskinesia: Involvement of Corticostriatal but Not Thalamostriatal Synapses

Abstract: We examined the structural plasticity of excitatory synapses from corticostriatal and thalamostriatal pathways and their postsynaptic targets in adult Sprague-Dawley rats to understand how these striatal circuits change in L-DOPA-induced dyskinesias (LIDs). We present here detailed electron and light microscopic analyses that provide new insight into the nature of the structural and synaptic remodeling of medium spiny neurons in response to LIDs. Numerous studies have implicated enhanced glutamate signaling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
158
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(180 citation statements)
references
References 77 publications
17
158
5
Order By: Relevance
“…The observation that L-DOPA fully restored the stepping deficit in striatal ChI-depleted parkinsonian mice also argues that the attenuated LID is not due to a decreased response to L-DOPA and further indicates the involvement of different neural circuitries underlying LID and akinesia. In addition to the possible involvement of cholinergic muscarinic receptors in LID (Ding et al, 2011), nicotinic acetylcholine receptor agonists have also been shown to reduce LID in partially DA denervated animals (Bordia et al, 2010;Quik et al, 2013), which is believed to occur through activation of presynaptic nicotinic receptors on DA terminals to promote DA release (Huang et al, 2011;Quik et al, 2013;Zhang et al, 2013; which may not be as significant in our model with near complete denervation), and release of glutamate from afferents from cortex and thalamus (Ding et al, 2008;Parikh et al, 2010). The importance of nondopaminergic transmitter systems that interact with dopaminergic projection in PD is apparent, and therefore pharmacologic agents directed toward serotonin, glutamate, adenosine, and cannabinoids are being investigated for potential anti-parkinsonian and anti-dyskinetic action (for review, see Pisani et al, 2007;Buck and Ferger, 2010;Oldenburg and Ding, 2011;Kalia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that L-DOPA fully restored the stepping deficit in striatal ChI-depleted parkinsonian mice also argues that the attenuated LID is not due to a decreased response to L-DOPA and further indicates the involvement of different neural circuitries underlying LID and akinesia. In addition to the possible involvement of cholinergic muscarinic receptors in LID (Ding et al, 2011), nicotinic acetylcholine receptor agonists have also been shown to reduce LID in partially DA denervated animals (Bordia et al, 2010;Quik et al, 2013), which is believed to occur through activation of presynaptic nicotinic receptors on DA terminals to promote DA release (Huang et al, 2011;Quik et al, 2013;Zhang et al, 2013; which may not be as significant in our model with near complete denervation), and release of glutamate from afferents from cortex and thalamus (Ding et al, 2008;Parikh et al, 2010). The importance of nondopaminergic transmitter systems that interact with dopaminergic projection in PD is apparent, and therefore pharmacologic agents directed toward serotonin, glutamate, adenosine, and cannabinoids are being investigated for potential anti-parkinsonian and anti-dyskinetic action (for review, see Pisani et al, 2007;Buck and Ferger, 2010;Oldenburg and Ding, 2011;Kalia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, long-term changes in gene expression, intracellular signaling pathways, neuronal plasticity, and morphology have all been linked to the expression of LIDs (Santini et al, 2009;Cenci and Konradi, 2010;Feyder et al, 2011;Huot et al, 2011;Rangel-Barajas et al, 2011;Zhang et al, 2013b). Moreover, these changes may occur via numerous neurotransmitter systems, such as the dopaminergic, glutamatergic, serotonergic, and others, which are all implicated in the development and maintenance of LIDs (Carta and Bezard, 2011;Huot et al, 2011;Blandini and Armentero, 2012;Duty, 2012;Rylander, 2012;Huot et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The list of target proteins includes cationic channels (60), membrane receptors (32,61) and membrane docking proteins (33). Since a wide variety of mechanisms underlie synaptic changes associated with LID, including abnormal dendritic spine increases in denervated D2R-containing striatal neurons (38) involved in corticostriatal synapses (62), several additional mechanisms could be related to DREAM-mediated changes in LID based on its presence in the cell body as discussed below.…”
Section: Lid-associated Phosphorylation Of Glur1 Is Attenuated In Dadmentioning
confidence: 99%